The Iraqi-Kuwaiti crisis in 1990 and regional and international positions on it - Nassif, Nazhan Hammoud (Journal of Tikrit University for Humanities, 2023)
The political relations between Iraq and Kuwait were often cautious, threats and contradictions, until the deterioration of relations reached a high level of military escalation ended with Iraq's invasion of Kuwait on 2 August 1990. Hence, the external intervention from its beginning to achieve desired goals represented fragmentation in Arab national security The failure of diplomatic means to deal with this crisis, from the beginning of its actions in situations of threats to international peace and security, the use of armed force to resolve this issue and the removal of Iraq from Kuwait, and the subsequent political and military events ended with the occupation of Iraq by the United States For American.